The Effect of High Glycemic Modified Breakfast Menu on Increasing Learning Concentration of Junior High School Students Insan Cendekia Mandiri (ICM) Sarirogo – Sidoarjo - Nurul Hindaryani; Erlyna Jayeng; Mujayanto (International Journal of Advanced Health Science and Technology, 2023)
The nutritional adequacy of the Insan Cendekia Mandiri (ICM) junior high school students is obtained from the provision of food in the dormitory. One way to increase the acceptance of food intake organized by the boarding institution at the Insan Cendekia Mandiri Junior High School (ICM) is to modify the food menu. The provision of food doesn’t escape the standard portion for each individual so takes a portion of food that is by the RDA, so that it can be seen whether the individual needs of junior high school students have been met or not. This study aims to analyze the effect of modifying the menu of a high-glycemic meal on the acceptability and increase in learning concentration in students of SMP Insan Cendekia Mandiri in Sarirogo, Sidoarjo. This research method uses a pre-experimental design with a one-group pretest-posttest to determine the quality of the modification of the high-glycemic plate menu through the level of preference, acceptance of the increase in learning concentration of junior high school students at Insan Cendekia Mandiri (ICM) Sarirogo, Sidoarjo. The research sample was 37 junior high school students taken by simple random sampling using a formula to meet the inclusion and exclusion criteria. The variables in this study consisted of independent variables, namely modification of high glycemic prescriptions, the dependent variable was acceptance and learning concentration. The research instrument used is a 7-day menu cycle using organoleptic tests by conducting pre and posttest. The result is The breakfast menu from ICM has a lower glycemic index than the modified menu because of the ingredients used. There is a difference in the average energy value in the modified menu, which is 102.5 kcal compared to the breakfast menu from ICM, 2,94 grams of protein average higher than the breakfast menu on ICM, 10,9 grams of fat higher than the breakfast menu on ICM and then 10,76 grams of carbohydrate average lower than breakfast menu on ICM, and student concentration has increased because of the modified menu which has a high glycemic index.